Anti-VEGF treatment of idiopathic, active choroidal neovascularization in patients below 45 years of age - Cywiński, Adam; Piwońska-Lobermajer, Anna; Świgoń, Małgorzata; Gacek, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The aim of the current work is to discuss the “off label” anti-VEGF therapy in patients under 45 years of age with idiopathic choroidal neovascularization within the macular area in the context of retrospective analysis of four patients (6 eyes), whose treatment started at different stages of the disease. Visual acuity improvement was achieved in 3 patients (5 eyes). In the fourth patient, the treatment was discontinued after one injection due to the lack of improvement. The degree of the improvement depended on the time of treatment initiation, location and severity of macular abnormalities. Anti-VEGF drugs provide good outcomes in idiopathic choroidal neovascularization, although this is an “off label” treatment. Treatment commencement at early stages of the disease increases chances for achieving and maintaining good visual function.